(untitled) (Revista Puertorriqueña de Psicologia, 2016)
The family plays a key role in the development and progression of substance use disorder (SUD) either by inducing risk, or promoting protection and resilience. However, only a limited number of studies have addressed how the families of individuals with SUD experience and perceive drug addiction and what attitudes toward treatment they show. The purpose of this study was to explore and describe how the parents of two Puerto Rican adult men with a history of SUD understand this phenomenon using an interpretative phenomenological analysis. Results show that parents perceived SUD as a negative phenomenon, but their arguments regarding their sons’ drug addiction contained several misconceptions. Parents believed that the rehabilitation process was dependent primarily on their sons’ willpower and intelligence, and they also considered trust to be one of the most important elements to obtain family support. We conclude that these parents used past experiences and their immediate social reality to construct particular conceptualizations of their sons’ SUD. Our findings provide important information about family perception and perspectives that can be used for SUD treatment and prevention strategies.